Dinamika ibadah gereja menggunakan Daring dimasa pandemi Covid-19 berdasarkan Ibrani 10:25 - Kingston Pandiangan; Stimson Hutagalung; Rolyana Ferinia (Sekolah Tinggi Teologi SAPPI Ciranjang, 2021)
The Covid-19 Pandemic has changed the model of worship. Online worship is the best option to minimize the transmission of Covid - 19. Therefore, the researcher wants to know whether the church members are ready to attend online services? The purpose of this study was to determine the extent to which the church’s vision, mission, interests, social interaction, and technology could be implemented by the church members. This research method is qualitative with a descriptive approach. The conclusion is that church members accept online worship and can still carry out social interactions strengthening and giving advice even through the learning process using gadgets. Members are fully aware that online evangelism is easier and spreads all over the world.